#TITLE_ALTERNATIVE# - ANDRIEANTO NURROCHMAN (NIM : 13705049); Pembimbing : Dr. Ir. Bambang Widyanto,
Corrosion is an interaction of metals with the environment, which react electrochemically, whether it is intentional and unintentional beneficial or even harmful. One form of corrosion that included into the 5 most important mechanisms of material degradation in the offshore and chemical sector is the erosion-corrosion. In the event of erosion-corrosion by fluid without solid particles, there are several mechanisms that can be generally grouped into three sections, the destruction occurs predominantly by corrosion, damage occurs by the combination of erosion-corrosion and destruction occurs predominantly by erosion. These three mechanisms are based on fluid velocity. At the destruction that occurred by a single fluid phase, corrosion rate accelerated by increasing turbulence and mass transfer due to the increasing speed, this phenomenon known as Flow-accelerated corrosion (FAC). This research was conducted with a variety of solutions for the fluid medium with 3.5% NaCl and 5% NaCl, and the speed variations are of 2.1 m / s, 4.42 m / s, 6.63 m / s and performed within 4 hours. Velocity variations are intended to be able to know the effect to the corrosion damage on St 37 carbon steel materials with a varied NaCl concentration. Weight loss was observed in the concentrations of 3.5% NaCl solution with the flow rate 2.10 m / s, 4.42 m / s, 6.63 m / s respectively are 0.050%, 0.049%, 0.018% , and in the solution with 5% NaCl concentration with the flow rate 2.10 m / s, 4.42 m / s, 6.63 m / s respectively are 0.038%, 0.046%, 0.038%. %. In the surface of the specimen, there is the flow pattern due to corrosion.